Pendidikan Islam Kreatif Era Industri 4.0 Perspektif Abuddin Nata - Aida Dwi Rahmawati (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sayyid Ali Rahmatullah Tulungagung, 2019)
Abuddin Nata is one of the figures, muslim intellectual, and writer who active in the development of Islamic study in Indonesia. This research aims to find new things about creative Islamic education through study psychological approach. This paper employed a library review research with explorative method. Then excavation and searching effort through assessment to books and article by Abuddin Nata’s, and reference books which related with that problem. In interpreting of Islamic studies which means a action oriented to guiding, directing, and building student do by conscious and planned in building a main personality suitable Islamic studies that is Qur’an and Sunnah. Presence of era of industry 4.0 in Islamic studies seen positive paradigm has been creative Islamic education. Consequently, teacher to be able makin ideal environment in optimizing potential of students. Creative Islamic education in era of industry 4.0 demand to could self-disrupting that is adjust with requirement and demand then future oriented.